EFFECTIVE MOTIVATION TOOLS IN THE MANAGEMENT OF PUBLIC SECTOR PERSONNEL AT THE REGIONAL LEVEL (INNOVATIVE ECONOMY, 2024)
Shyshpanova N.O. EFFECTIVE MOTIVATION TOOLS IN THE MANAGEMENT OF PUBLIC SECTOR PERSONNEL AT THE REGIONAL LEVELPurpose. The aim of the study is to describe effective motivation tools in the management of public sector personnel at the regional level.Methodology of research. General scientific methods were used during the study, namely: description, analysis, synthesis, induction and special research methods, namely: logical and semantic (used to define and clarify basic terms and concepts), historical and legal (became the basis for analysing the development of legislative and regulatory aspects of determining motivation tools in public sector personnel management), structural and functional (for analysing existing shortcomings in the motivational system of the public service).Findings. The main problems of staff motivation in the civil service of Ukraine are analysed in the study. In particular, insufficient attention is paid to the individual needs of employees, which makes it difficult to identify effective incentives to improve performance. It is also found that the psychological climate in teams remains without proper attention, which negatively affects employee engagement.The author describes that the legal framework, in particular the Law of Ukraine ???On Civil Service’, creates general conditions for material motivation, but in practice, bonus payments do not always depend on performance. This reduces the incentive function of bonuses, which makes it impossible to actively encourage employees to improve efficiency.Recommendations are developed for the introduction of new motivation mechanisms, such as regular performance evaluations and increasing the role of non-material incentives. Proposals are made to improve the psychological climate through team building activities and training seminars.Originality. The scientific novelty of the study lies in the fact that the establishment of the dependence of the effectiveness of motivational tools in the public sphere on a comprehensive approach that integrates material and non-material incentives is substantiated. A special contribution is the emphasis on the regional level of management; where for the first time the need to take into account local specifics and social and economic conditions in the process of selecting motivational tools is substantiated. It was found that the use of these measures will contribute not only to increasing the effectiveness of personnel work, but also to strengthening public trust in public institutions and the development of local communities.Practical value. Specific recommendations for improving motivational mechanisms in the public service have been developed. The implementation of the recommendations can increase the efficiency of public administration at the regional level, which will contribute to both the development of local communities and strengthening trust in government bodies. The application of the research results will allow optimising work with staff and improving the psychological climate in public institutions.Key words: motivation, incentives, management, personnel, public sphere.
Keywords: motivation; incentives; management; personnel; public sphere.